2014
DOI: 10.1007/s40258-014-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Spillover Effects of Illness on Parents, Spouses, and Children of the Chronically Ill

Abstract: Background Given the broad scope of the spillover effects of illness, it is important to characterize the variability in these outcomes in order to identify relationship types in which secondary impacts of illness are particularly important to include in health economic evaluations. Purpose To examine heterogeneity in spillover effects of chronic conditions on family members by type of familial relationship with patient. Methods Adults (≥18 years) and adolescents (13-17 years) who had a parent, spouse or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 35 publications
0
44
1
Order By: Relevance
“…We also did not find any spillover effects on non-caregiving family members who also may be affected. Both populations are important to study because the spillover effects of illness may arise through both a "caregiving effect" and a "family effect", that is, the impact a family member's sickness has on someone who shares an emotional bond with that ill person [16,88,89]. Therefore, the AD/dementia spillover effects of studies in our review may be underestimated because of these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not find any spillover effects on non-caregiving family members who also may be affected. Both populations are important to study because the spillover effects of illness may arise through both a "caregiving effect" and a "family effect", that is, the impact a family member's sickness has on someone who shares an emotional bond with that ill person [16,88,89]. Therefore, the AD/dementia spillover effects of studies in our review may be underestimated because of these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review suggests substantial variation in the likelihood of spillover by context (Wittenberg and Prosser, ). Recent evidence indicates that spillover impacts are likely to be greatest when dealing with childhood and mental health conditions (Wittenberg et al , , Lavelle et al , ). As many of the survivors in this study were children with psychological problems, it seems likely that our spillover estimates would be at the higher end of the spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings of the present study are inconsistent with these results given that the reported prevalence of depressive symptoms was the same in the youngest age group (<45 years) and the oldest age group (>60 years; Table ). Adverse effects may be easily understood as the spillover effect of cancer history in the family on depressive symptoms experienced by relatives, but a full explanation requires further consideration of various interacting factors including bereavement , relationship types , and experienced burden levels of caregiving .…”
Section: Discussionmentioning
confidence: 99%